Design of heat exchanger network using pinch method - Wan Mansor, Wan Nurdiyana (2006)
Chemical or oil refineiy processes utilize huge amounts o f energy in their routine operations. Therefore, it is vital for such industries to find ways o f maximizin g the use o f energy and make the system more efficient through reduction in energy, water and raw material consumption. Wast e energy can be transferred to another process and that wil l increase the profitability o f the industries. Whe n the use o f a heat exchanger network (HEN) is considered for these tasks, the framewor k developed in this study can be implemented to mak e a cost-benefit analysis. This thesis represents a framewor k for generating the HE N over a specified range o f variations in the flo w rates and temperature o f the streams. So that the heat exchanger area, numbe r o f heat exchange units and load on the heat exchangers can be estimated. T he proposed method to analyze and design the HE N is called pinch method, which is one o f the most practical tools and used to improve the efficiency o f energy usage, fuel and water consumption in industrial processes. This method investigates the energy flows within a process and identifies the most economical ways o f maximizing heat recovery. This method consists o f five major steps to follow, which wil l finally lead to H E N design. Th e steps are: (1 ) choose a minimu m temperature approach temperature (DTmin) , (2 ) construct a temperature interval diagram, (3 ) construct a cascade diagram and determine the minimu m utility requirements and the pinch temperature, (4 ) calculate the minimu m number o f heat exchangers above and below the pinch and (5) construct the heat exchanger network. T h e emphasis o f this work has been on the designing o f the HEN . However, to demonstrate the practical implications o f pinch analysis, DTmi n and the heat exchanger costs, it is necessary to estimate the heat transfer area o f the HEN , which wil l help in arriving at the total cost including capital and running costs o f the designed HEN . Th e effect o f changing the DTmi n gave a good indication on the overall costs.